Factors associated with zidovudine substitution in HIV/AIDS patients attending Badung Hospital, Bali, Indonesia between 2006-2014 - Adnyani, Sukma; S., Sawitri A. A.; L., Wulandari; A., Swandewi; P., Artawan E.; J., Reekie; N., Wirawan D. (International Journal of Research in Medical Sciences, 2016)
Background: Zidovudine (AZT) is the most commonly used drug in first line antiretroviral therapy (ART) in Indonesia; however, substitution due to its side effect is common. The majority of HIV positive patients in Badung Hospital Bali are treated with AZT yet no longitudinal studies in Bali have investigated the number of substitutions or the factors associated with it. Methods: A retrospective cohort study of HIV positive persons aged >15 years, receiving AZT between 1st January 2006 – 31st August 2014 was conducted. Persons were included from their date of starting AZT. Cox proportional hazard models were applied to estimate the risk and time to substitution. Substitution was defined as single drug change due to side effects and initiating another drug of the same class. Results: During our study 260 patients started AZT, of which 77 (29.6%) experienced substitution. The risk of substitution was 19 per 100 person years. Of those 77, the median time to AZT substitution was 69 days (IQR 25-178). Factors significantly associated with an increased risk of AZT substitution included women (HR 1.79; 95% CI 1.09-2.94), having low hemoglobin levels <10g% (HR 2.72; 95% CI 1.02-7.21), clinical stage III and IV (HR 3.53; 95% CI 1.26-6.19) at the time of starting AZT, and starting ART after 2012 (HR 3.83; 95% CI 2.19-6.70). Conclusions: Present study identified individuals that may be at a high risk of AZT substitution who should be monitored more closely or consideration given to initiating them on another treatment regimen.